Region‐Dependent and Stable Ferroelectric Photovoltaic Effect Driven by Novel In‐Plane Self‐Polarization in Narrow‐Bandgap Bi2FeMo0.7Ni0.3O6 Thin Film. Issue 3 (3rd December 2018) - Li, Yong; Cui, Xiaxia; Sun, Ningning; Du, Jinhua; Li, Xiaowei; Jia, Guixiao; Hao, Xihong
Abstract: Ferroelectric polarization is a crucial factor to induce photovoltaic (PV) effect in ferroelectric materials. Here, a novel in‐plane self‐polarization is found for the first time in a polycrystalline Bi2 FeMo0.7 Ni0.3 O6 thin film prepared by the sol–gel process. Different from out‐of‐plane polarization with uniform orientation in the vertical direction, the in‐plane self‐polarization exhibits radialized orientation which points from the center of the thin film to its edges in the horizontal direction. It is demonstrated that the forming of the self‐polarization is attributed to the internal electric field caused by NiBi dipoles. The peculiar polarization induces the region‐dependent ferroelectric PV effect and rectification behavior in the horizontal direction of the thin film. Moreover, in a long time and wide temperature range, the thin film maintains the stable PV properties due to the constant self‐polarization state. This work makes a new cognition for the nature of ferroelectric polarization, and it highlights the Bi2 FeMo0.7 Ni0.3 O6 thin film as a PV and electronic material for peculiar photoelectric devices. Abstract : A novel in‐plane self‐polarization with radialized polarization orientation is found in ferroelectric Bi2 FeMo0.7 Ni0.3 O6 thin film with narrow bandgap. The peculiar polarization induces a region‐dependent ferroelectric photovoltaic (PV) effect and rectification behavior. The in‐plane self‐polarization state leads to an outstanding stability of the PV properties in long time and at variable temperature.